2014
DOI: 10.1200/jco.2013.48.8551
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Laparoscopic Gastrectomy for Gastric Cancer: A Large-Scale Case-Control and Case-Matched Korean Multicenter Study

Abstract: The long-term oncologic outcomes of laparoscopic gastrectomy for patients with gastric cancer were comparable to those of open gastrectomy in a large-scale, multicenter, retrospective clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
181
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(200 citation statements)
references
References 21 publications
18
181
1
Order By: Relevance
“…The 5-year survival rate of 98.2% for both OS and RFS is comparable with that of previous retrospective studies assessing laparoscopic gastrectomy [10][11][12]. For open surgery, Nashimoto et al [13] Kim et al [12] reported the OS after matching for the operation method and surgeons did not show any significant differences between open gastrectomy and laparoscopic gastrectomy for all stages of cancer.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The 5-year survival rate of 98.2% for both OS and RFS is comparable with that of previous retrospective studies assessing laparoscopic gastrectomy [10][11][12]. For open surgery, Nashimoto et al [13] Kim et al [12] reported the OS after matching for the operation method and surgeons did not show any significant differences between open gastrectomy and laparoscopic gastrectomy for all stages of cancer.…”
Section: Discussionsupporting
confidence: 72%
“…For open surgery, Nashimoto et al [13] Kim et al [12] reported the OS after matching for the operation method and surgeons did not show any significant differences between open gastrectomy and laparoscopic gastrectomy for all stages of cancer. A recent observational study of 1848 stage I gastric cancer patients adjusted the backgrounds using propensity matching with confounding factors to demonstrate favorable long-term survival of LADG patients compared with ODG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although a minimally invasive surgical approach has received general acceptance [2][3][4], gastric cancer surgery remains a high-risk procedure that is associated with clinically significant postoperative stress, postgastrectomy syndrome, and other complications. The morbidity and mortality rates after radical gastrectomy have been reported as 9.1-28.1% and 0-1.3% respectively [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of minimally invasive surgical methods are proven and well published [6,[10][11][12][13][14][15][16]. With advantages such as decreased postoperative pain and shorter length of hospital stay, minimally invasive techniques are heralded as a significant development in the progress of general surgery.…”
Section: Introductionmentioning
confidence: 99%